Analysis of breastfeeding status and influencing factors among healthcare workers in Southwestern China - Tingting Dai; Jiaxin Wan; Qiuyue Liu; Xiaoyan Liu; Cheng Chen (International Breastfeeding Journal)
Abstract Background This study aims to evaluate the current status of breastfeeding practices among healthcare workers in Southwest China, identify key factors influencing their exclusive breastfeeding (EBF), and provide targeted recommendations for increasing the EBF rate and prolonging EBF duration in this population. Methods A cross-sectional survey was conducted among 685 healthcare workers who were ≥ 6 months postpartum, with data collected from January 2019 to January 2024. The questionnaire included items on general demographics, breastfeeding knowledge, and breastfeeding practices. Exclusive breastfeeding (EBF) was defined as feeding infants only breast milk from birth, with no other foods or drinks (including water) provided. Logistic regression analysis was performed to identify factors influencing EBF, and based on the results, a nomogram prediction model was constructed and validated using R software. Results A total of 685 participants were enrolled in this study, among whom 363 (53.0%) had exclusive breastfeeding durations of less than 5 months (Group A) and 322 (47.0%) continued exclusive breastfeeding for 6 months (Group B). The primary sources of breastfeeding knowledge were the internet and professional consultations, while common barriers included nipple/breast problems and work-related factors. Logistic regression analysis identified four independent factors associated with the continuation of exclusive breastfeeding for 6 months (all p < 0.05): parity (OR 1.86; 95%CI 1.35, 2.58), breastfeeding consultations during pregnancy (OR 1.44; 95%CI 1.04, 2.00), three-shift work resumption (OR 1.67; 95%CI 1.32, 2.10), and family support for breastfeeding (OR 1.90; 95%CI 1.07, 3.37). A nomogram prediction model constructed based on these factors showed an area under the ROC curve of 0.75 (95% CI 0.70, 0.81), indicating good predictive performance with high consistency between predicted and observed outcomes. Conclusion Healthcare institutions should actively provide breastfeeding consultation services, encourage postpartum healthcare workers to delay participation in shift work, and strengthen breastfeeding education to enhance public awareness. These measures will help improve the exclusive breastfeeding rate among infants under 6 months of age.